How life cycle costs criteria may be used for design life and/or replacement cycle - Edvardsen, Carola (2015)
fib Commission 8 Durability (formally fib Commission 5 Service Life Design) recently initiated a new Task Group with defined terms of reference to provide guidelines to owners, contractors, academics, financial institutions and Engineers on the long-term benefits of considering Life Cycle Costs. The Life Cycle Costs Task Group draws upon the experience of consultants, researchers and owners and this paper presents the aim and scope of the task group.